Sexual life of Japanese patients with erectile dysfunction taking phosphodiesterase type 5 inhibitors: An Internet survey using the Psychological and Interpersonal Relationship Scales‐Short Form questionnaire. (24th March 2014) - Tsujimura, Akira; Kiuchi, Hiroshi; Soda, Tetsuji; Takezawa, Kentaro; Okuda, Hidenobu; Fukuhara, Shinichiro; Takao, Tetsuya; Nonomura, Norio; Miyagawa, Yasushi
<x xml:space="preserve">Abstract</x> Objectives To investigate details of sexual function of erectile dysfunction in Japanese patients taking phosphodiesterase type 5 inhibitors. Methods A Japanese version of the Psychological and Interpersonal Relationship Scales‐Short Form was used to carry out a nationwide survey using the Internet. A total of 556 erectile dysfunction patients (age 30–70 years) who had been prescribed a phosphodiesterase type 5 inhibitor and had attempted sexual intercourse within the past 6 months were included in this survey. Scores were compared in relation to the phosphodiesterase type 5 inhibitors most frequently taken within the past 6 months. Results In the subdomains of self‐confidence and spontaneity of the Psychological and Interpersonal Relationship Scales‐Short Form, scores for vardenafil and tadalafil were significantly higher than those for sildenafil. In the subdomain of time concern of the Psychological and Interpersonal Relationship Scales‐Short Form, the score for tadalafil was significantly lower than that for others. Conclusions Our findings support the hypothesis that Japanese patients with erectile dysfunction have high sexual self‐confidence, spontaneity and low time concerns when taking tadalafil. These characteristics of tadalafil could be associated with high patient satisfaction and high preference.